UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF EXAMPLE NON EXAMPLES SISWA KELAS I SD NEGERI 012 PANGKALAN BARU KECAMATAN SIAK HULU - Zaitun (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this study is the low activity and learning outcomes of Civics students in grade 1 012 SD Negeri 012Pangkalan Baru, for this reason, improvements are made to learning through classroom action research using example non- example learning models. The purpose of this study is to increase Civic Education activities and learning. This research is a classroom action research conducted at SD Negeri 012 Pangkalan Baru. The subjects of this study were grade 1 students with 23 students. This study was carried out in two cycles, which were carried out in four stages: planning, implementation, observation, and reflection. The results of the study showed that students' learning activities had increased, in cycle 1 meeting 1 in the very good category got 28.99%, in the good category was 29.13%, in the sufficient category was 31.88%, and in the poor category was 10 00%. At meeting 2 in the very good category was 46.38%, in the good category was 31.88%, in the sufficient category was 21.74%, and in the less category was 5.00%. In cycle 2 meeting 1 activity in the very good category was 53.62%, in the good category was 33.33%, in the sufficient category was 13.04%, and in the poor category was 4.60%. At meeting 2 in the very good category was 73.91%, in the good category was 18.84%, in the sufficient category was 7.25%, and in the less category was 0.00%. In addition, student learning outcomes have increased, in cycle 1 meeting 1 the number of students who completed was 18 students (78.26%), at the second meeting reached 21 students (91.30%). In cycle 2 meeting 1 reached 19 (82.61%), and at themeeting of 2 to 20 students (86.96%).